PERANCANGAN LAMPU JALAN BERBASIS SOLAR CELL DI LABORATORIUM TEKNIK UNIVERSITAS ISLAM MAKASSAR - Sriwati; Khaidir, Muhammad; Faridah; Syarif, Muhammad Alfian; Syarif, Suhal Farwadi (Jurnal INSYPRO (Information System and Processing), 2024)
Indonesia is located on the equator, so Indonesia has abundant sources of solar energy with an average solar radiation intensity of around 4.8 kWh/m2 per day throughout Indonesia. This research aims to make the Sollar Cell an alternative for Public Street Lighting (PJU) which is a Solar Public Street Lighting (PJUTS) system, the ability of this system to generate and store electrical energy makes it a reliable system to supply street lamp energy. Testing is carried out with two types of tests, namely primary data measurement and secondary data measurement. In the field test, it is carried out through direct measurement of the potential for solar radiation and at the location of the street light pole to be installed, while secondary data is obtained from a body or authority that has the authority to publish radiation data, in the case we use satellite image data from NASA through the NASA-Langley Distributed Archive. The test was carried out by testing where the street lamp was tested for one day by being directly loaded with the battery and the two solar panels to charge the battery. In field testing, the panel will charge the battery with an average input of 298.79 W and an output of 298.76 with an average effectiveness of 10.02%, the battery is charged with LED lights at night which uses 7% of the total electrical power needed, which is 30 Watts from 300 Watts. When testing in the field peak load or when all loads are operating has never occurred, when a peak load occurs , the required electrical power is 380.6 Watts.